Software as a service adoption determinants - the role of software asset characteristics - Rintakoski, Miika (My University, 2018)
Software as a service is constantly gaining market share from traditional on-premise licensing. Despite the trend, cloud application market share is still just about 18 % of total software market. Organizations are continuously evaluating new software alternatives. The selection between SaaS and on-premise solutions is a key decision that organizations need to make when procuring new software. In order to succeed in software procurement decisions, organizations need to develop their own decision-making process and understand the potential opportunities and risks they need to consider in these decisions. This research addresses these determinants which affect the software as a service adoption decision making. This research is built on existing literature about SaaS adoption. The adoption determinants identified in the literature were used as a basis for semi-structured interviews conducted in IT organizations. This research evaluates whether the adoption determinants found in the literature affect decision-making in the researched organizations and to what degree these adoption determinants vary depending on the procured software asset. Theoretical background combines factors from technological, organizational and environmental elements and combines the asset-specific characteristics into them. The results of this research show that the asset-specific variance is significant in many technological, organizational and environmental adoption determinants. In addition to those, direct asset-specific determinants were identified. Determinants such as security, existing IT landscape and regulation are evaluated differently depending on the software asset. Even if there were determinants that are treated in a universal manner, each software and its applicability for SaaS deployment needs to be evaluated separately. Conclusion is that organizations need to evaluate their SaaS adoption comprehensively from technological, organizational and environmental aspects. General high-level principles can be set for the SaaS adoption as long as each asset and its characteristics are still considered individually.
Keywords: Software as a service, cloud software, IT adoption, determinants